Integrating physiotherapy in rural primary health care: Early lessons on the value, feasibility, and emerging role of the physiotherapist from a community-oriented primary care (COPC) program in Rajasthan, India - Colis Anwari; Deekshita Yadav; Gargi Goel; B. C. Rao; Pavitra Mohan; Ramakrishna Prasad (Journal of Family Medicine and Primary Care, 2024)
Background: Physiotherapists are health professionals who enhance mobility and quality of life (QoL) through clinical reasoning and the application of evaluation and treatment strategies. Their role is crucial in promoting health, preventing injury, and maintaining function. AIM: This paper aims to (1) share early experiences and learnings from integrating physiotherapy in rural primary health care, (2) discuss the scope and role of physiotherapists in the primary care team, (3) list the competencies of physiotherapists in rural primary care settings, and (4) advocate for a re-imagined role of physiotherapists as multi-skilled “primary care physiotherapists.” Setting and Method: Using a selection of case stories from rural primary health care settings, the paper provides insights into the integration and impact of physiotherapy within these communities. Results: The integration of physiotherapy in rural primary health care has demonstrated significant benefits in promoting comprehensive primary health care. The case stories highlight the expanded scope and essential competencies of physiotherapists as vital members of the primary care team. Conclusion: This paper emphasizes the critical role physiotherapy plays in primary health care and calls for broader recognition and support for physiotherapists. It underscores the need for a re-imagined perspective of physiotherapists in rural settings, advocating for their role as multi-skilled primary care professionals.